Classroom Techniques In Teaching Speaking To The 7th Grade Students Of Smp N 2 Banyudono In 2016/2017 Academic Year - Sulistya Pambudi, Wahyu; , Mauly Halwat Hikmat, Ph.D (2017)
The objectives of this research are to describe the kinds of classroom techniques used by teacher in teaching speaking, the purpose of using each classroom technique, teacher's role, and student's role in SMP N 2 Banyudono. This research used descriptive qualitative research. Techniques for collecting data were observation and interview. The subjects of this research were English teacher and students of 7THG grade class. To analyze the data the writer reduced, displayed, and verified the data. The findings of this research show that there are some techniques used by English teacher of SMP N 2 Banyunono to develop speaking skill of the students, namely: role-playing, song, and discussion technique. The purpose of role-playing in learning process is to improve vocabulary and fluency 7THG grade students to speak English. The purpose of song technique is to teach pronunciation and vocabulary, and the purpose of discussion technique in teaching learning process is to make students active and confident to speak up. The roles of English teacher take place in 7TH grade class as: a) manager, b) motivator, c) quality controller, and d) group organizer. The student's role of 7TH grade class of SMP N 2 Banyudono is as: 1) the planner, 2) member of a group, 3) tutor of other learners, and 4) the learners who learn from the teacher. Keywords: classroom techniques in teachhing speaking, the purpose of classroom tehniques, teacher's role, and student's role